Pemaknaan Cerpen Hitokui Neko Karya Murakami Haruki - Zaki Ainul Fadli (Diponegoro University, 2019)
(Title: The Interpretasion of Murakami Haruki’s Hitokui Neko) This article aims to reveal the meaning of cats in the short story of Hitokui Neko. The method used is a structural method, namely by analyzing the basic narrative structure of the short story and the main marker of the short story. Then the interpretation of the meaning of the cat in a short story is carried out both in the first or second level interpretation. The results of the analysis show that there are three meanings of cats in the short story of Hitokui Neko. First, denotative-associative meaning. Cats are interpreted as pets, but are also used as associative meanings for children. The use of this associative meaning is used by Izumi when she wants to know the response of “I” if Izumi is pregnant and then has children. Secondly, cats are denotative-neutral, meaning cats as human pets in general. The use of denotative-neutral meanings can be seen, among others, when “I” tells of his experience of losing his pet cat. Third, denotative-mystical meaning. This meaning appears in the hallucinations of “I”. A cat that is likened to a witch Macbeth appears as an antagonistic force that eats “I” without resistance.